2022
DOI: 10.3390/toxics10100567
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals in Cannabis Seized by Law Enforcement in Ghana and Multivariate Analysis to Distinguish among Different Cannabis Farms

Abstract: For hundreds of years, cannabis has been one of the most known cultivated plants due to its variety of uses, which include as a psychoactive drug, as well as for medicinal activity. Although prohibiting cannabis products, the countries of the African continent are the largest producers of cannabis in the world; a fact that makes the trafficking of cannabis-based illicit drugs a high priority for local law enforcement authorities. The latter are exceedingly interested in the use of chemical analyses for facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, there is a case series of 95 patients with lead toxicity due to Pb contamination of cannabis to increase its weight [ 65 ]. Also, some documents reveal high levels of Pb and As in the cannabis samples [ 66 , 67 ], which are more than the permissible amount for medicinal plants determined by the World Health Organization [ 67 ]. Based on another finding of the current study, there were no significant differences in trace element levels in different sub-groups of drug users.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is a case series of 95 patients with lead toxicity due to Pb contamination of cannabis to increase its weight [ 65 ]. Also, some documents reveal high levels of Pb and As in the cannabis samples [ 66 , 67 ], which are more than the permissible amount for medicinal plants determined by the World Health Organization [ 67 ]. Based on another finding of the current study, there were no significant differences in trace element levels in different sub-groups of drug users.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the quality of cannabis and the potential risk of use, it is necessary to monitor all these compounds. Dourvis et al showed that cannabis samples in Ghana have high levels of As and Pb, which are toxic elements [48].…”
Section: Discussionmentioning
confidence: 99%
“…A study of the analysis of Cannabis seized in Ghana followed by chemometric methods to try and classify different production farms was reported by Douvris et al 295 Twelve analytes (As, Ca, Cd, Cu, Fe, Hg, K, Mg, Mn, Na, Pb and Zn) were determined using ICP-MS following a microwave-assisted acid digestion (in the presence of hydrogen peroxide). Also sampled and digested were soil samples from three known cannabis farms.…”
Section: Forensic Applications Of Glass Analysismentioning
confidence: 99%